2021
DOI: 10.1038/s41598-021-93832-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for COVID-19 detection based on CT images

Abstract: COVID-19 has tremendously impacted patients and medical systems globally. Computed tomography images can effectively complement the reverse transcription-polymerase chain reaction testing. This study adopted a convolutional neural network for COVID-19 testing. We examined the performance of different pre-trained models on CT testing and identified that larger, out-of-field datasets boost the testing power of the models. This suggests that a priori knowledge of the models from out-of-field training is also appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 54 publications
0
78
0
Order By: Relevance
“…Among the most recent ones [46,47], 3D images could be handy to avoid losing the interstitial information of the lungs. However, several works have exploited 2D images showing the property of extracting representative features of COVID-19 lesions for disease detection [48][49][50][51][52][53][54][55][56]. They are all CNN-based and used CT [48][49][50][51][52][53][54][55] or CXR [43,50,56] images.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the most recent ones [46,47], 3D images could be handy to avoid losing the interstitial information of the lungs. However, several works have exploited 2D images showing the property of extracting representative features of COVID-19 lesions for disease detection [48][49][50][51][52][53][54][55][56]. They are all CNN-based and used CT [48][49][50][51][52][53][54][55] or CXR [43,50,56] images.…”
Section: Related Workmentioning
confidence: 99%
“…However, several works have exploited 2D images showing the property of extracting representative features of COVID-19 lesions for disease detection [48][49][50][51][52][53][54][55][56]. They are all CNN-based and used CT [48][49][50][51][52][53][54][55] or CXR [43,50,56] images. We particularly focused this study on deep learning-based classification methods for COVID-19 detection.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods train the weights of the network on large datasets and fine-tune the weights of the pretrained network using small datasets. Because only a limited amount of data is present in the current CXR datasets, the use of transfer learning is extremely important for effective COVID-19 detection [29]. With transfer learning, Apostolopoulos and Mpesiana [30] detected various abnormalities from small X-ray images; the results showed that deep learning with X-ray imaging utilizing transfer learning could successfully extract biomarkers related to the COVID-19 disease.…”
Section: Related Workmentioning
confidence: 99%